Agitated Behavior and Activities of Daily Living Retraining During Posttraumatic Amnesia. Issue 5 (September 2018) - Trevena-Peters, Jessica; Ponsford, Jennie; McKay, Adam
Abstract : Background: Patients in posttraumatic amnesia (PTA) may receive limited rehabilitation due to the risk of overstimulation and agitation. This assumption has not been tested. Objective: To examine the relationship between agitated behavior and participation in therapy for retraining of activities of daily living (ADL) while in PTA. Setting: Inpatient rehabilitation center. Participants: A total of 104 participants with severe traumatic brain injury, admitted to rehabilitation, in PTA of more than 7 days. Intervention: ADL retraining during PTA followed errorless and procedural learning principles. Design: Group comparison and regression modeling of patient agitation data from a randomized controlled trial comparing ADL retraining in PTA (treatment) versus no ADL retraining in PTA (treatment as usual, TAU). Outcome Measures: Agitation using the Agitated Behavior Scale. Therapy participation measured in minutes and missed sessions. Results: There were no group differences in agitated behavior (average scores, peak scores, or number of clinically agitated days) between the treatment and TAU groups. For treated patients, there was no significant relationship between agitation and therapy participation (therapy minutes or missed ADL treatment sessions). Conclusions: This study demonstrated that agitation is not increased by delivery of structured ADL retraining during PTA and agitation did not limit therapy participation. This supports the consideration of active therapy during PTA. Abstract : Supplemental Digital Content is Available in the Text.